(untitled) (Педагогіка вищої та середньої школи, 2007)
In an offered material system questions c f creative activity, since perception through installation and further to concept transforming (art) activity are considered. Given article is called to order creative work of the future artist-teacher and to make its less spontaneous, having armed with his clear data concerning bases of art creative activity.